Youth Response to Tasya Farasya as Wardah Cosmetic Promotion Media: Respon Remaja pada Tasya Farasya sebagai Media Promosi Kosmetik Wardah - Devi Selvia Ramadhanni; Ainur Rochmaniah (Academia Open, 2024)
This study aims to investigate the adolescent reception of beauty vlogger Tasya Farasya as a promotional medium for Wardah cosmetic brand through her YouTube video titled "Simple Makeup Tutorial for Beginners! Also, Wardah Colorfit Series Review." Employing a qualitative approach with Stuart Hall's decoding-encoding model, data collection involved in-depth interviews and observation using purposive sampling. The analysis revealed that 8 informants positioned themselves in a dominant hegemonic stance, while 2 informants engaged in negotiation. All informants acknowledged Tasya Farasya's provision of clear and educational information about Wardah products, capturing the attention of a substantial audience. This study contributes valuable insights into the dynamics of beauty vlogger influence on youth, emphasizing the informative and engaging aspects of Tasya Farasya's content. Highlights : Influential Content Creator: Tasya Farasya emerges as a significant influencer, impacting the perceptions of youth towards beauty products and brands. Educational and Engaging: The study underscores Tasya Farasya's role in providing clear and educational information about Wardah cosmetics, contributing to an engaging viewer experience. Hegemonic Dominance and Negotiation: Eight informants align with a hegemonic dominant stance, while two engage in negotiation, revealing the varied and complex reception dynamics among the audience. Keywords: Beauty vlogger, Tasya Farasya, Wardah cosmetics, Youth reception, YouTube.